Determinants of health-related productivity loss: Investigating the link between workaholic tendencies and presenteeism in the public sector - Astriningrum, Karomah Devi (Asian Journal of Toxicology, Environmental, and Occupational Health, 2026)
Background: Presenteeism is the behavior of workers who are present to do their work when they experience health problems. Presenteeism behavior is quite worrying because it can harm the company and also worsen health. This research aims to determine the most dominant factors in the level of presenteeism at Institution X in 2023. Methods: The research used a cross-sectional study design and data was obtained directly by filling out a questionnaire (primary data). The research was conducted in November – December 2023 using a sample of 205 PPNPN employees at a Non-Ministerial Government Institution in Central Jakarta. Data analysis used the Chi-Square and Multiple Logistic Regression tests to achieve research objectives. Findings: Univariate analysis revealed that 59.5% of employees experienced high presenteeism, while 67.3% exhibited workaholic tendencies. After being controlled for job satisfaction, the analysis results show that workaholic ($P < 0.001$; POR = 3.703; 95% CI = 1.8–7.6) is the factor that dominates the level of presenteeism. Furthermore, the analysis confirmed that demographic characteristics (gender, age, education, and marital status) and job insecurity did not have a significant relationship with presenteeism levels ($P > 0.05$). Conclusion: The existence of presenteeism behavior can be a concern for institutions to create a good work environment so that the prevalence of presenteeism can decrease and employees maintain productivity without harming their health. Novelty/Originality of this article: This study identifies workaholism as the most dominant factor influencing presenteeism among non-ministerial government employees, highlighting the importance of addressing workplace culture in mitigating health-related productivity loss.